Kajian Pola Percepatan Penanganan Stunting di Kota Banjarmasin Study on the Acceleration Pattern of Stunting Management in Banjarmasin City - Masdiputri, Sri Nuriaty; Hermina, Ceria; Ariani, Lita; Nadia, Hafizhatu; Sari, Rohni Taufika (UKInstitute, 2024)
The Ministry of Health emphasizes that stunting is a condition of growth failure due to prolonged nutritional deficiencies, exacerbated by inadequate catch-up growth. Stunting is a complex issue requiring specific and multisectoral interventions. This study aims to examine the acceleration pattern of stunting management in Banjarmasin City. A mixed-methods approach was employed using an embedded strategy, where the primary method was qualitative, and the secondary method was descriptive quantitative. Informants were selected through purposive sampling from the pentahelix components, with data analysis following the Miles and Huberman model. The study's recommendations include a psychoeducation program for families at risk of stunting, formalized through a memorandum of understanding (MoU) and an implementation guideline; a mayoral policy for relevant SKPDs based on the Internal Quality Assurance System (SPMI) cycle (PPEPP); recruitment and training of Posyandu cadres; an integrated stunting master data system; community leader involvement in program outreach; and the establishment of a monitoring and evaluation team with scheduled indicators